The Effect of Teaching with the Personal Learning Method (Claire’s Plan) On the Performance and Teaching of Some Artistic Gymnastics Skills for Female Students Aged (11-12) Years in Baghdad Governorate - Kylan Mahmoud, Baida (International Journal of Psychosocial Rehabilitation, 2020)
Artistic gymnastics occupies an important place among individual sports, and this importance came because it is an interesting game in addition to that it can achieve good results for the country, and gymnastics works on forming the structure and the body and giving it good strength and enjoyment of high physical fitness, and since it is an individual game it provides an opportunity that is not limited to creating the ability to innovate and succeed when performing movements, which leads to the development of the ability to embody coordination, continuity, and compatibility between players. Given the importance of artistic gymnastics and the importance of teaching methods in teaching and learning the technical skills of gymnastics for students between the ages of 11 and 12 years, researcher Z considers the necessity of finding modern teaching methods with the age stage that are consistent with their preferences and desires and move away from the traditional way in which the individual differs The Aryan, therefore, one of the methods of individual education was addressed, namely (personal learning, "Claire’s plan"), because individual education is the process by which the learner tries to acquire by himself the sufficient amount of skills through training according to the skills installed in the program in addition to the use of educational devices and situations. . The importance of the research lies in the fact that it is an attempt by the researcher to use a new educational and educational method in developing the level of performance in some technical gymnastics skills for students between the ages of 11 and 12 years. The research aims to - Identifying the effect of using the method (personal learning, "Claire’s plan") on improving the level of performance in some skills in artistic gymnastics for female students (11-12) years old in Baghdad governorate. As for imposing research, it is - There are statistically significant differences in the method (personal learning, "Claire’s plan") in some technical skills for students’ body ages (11-12) in Baghdad governorate in the pre-tests and dimensions in favor of the post-test.